Kinetic isotope effect of decomposing fatty acids in the continental shelf sediment of the northern South China Sea - Tengteng Wang; Chuhan Lin; Han Zhang; Jiying Li; Lifang Wang; Yaohua Luo; Jie Liu; Jiaheng Shen; Tiantian Tang; Tiantian Tang (Frontiers in Marine Science, 2024)
As a response of the coastal oceans to more severe anthropogenic disturbance, increasing coastal primary production has been more frequently observed in recent years. This raises the question of how this progressive change reshapes the long-term carbon sequestration in the coastal oceans. With this question in mind, we investigated the sediment organic matter (OM) preserved on the shelf of the northern South China Sea (NSCS) where high primary production has been observed. Across this sediment core, relatively low total organic carbon content of around 0.60% was observed. Fatty acids with less carbon numbers exhibit exponential decreases downward with degradation rate constants ranging from 0.10 to 0.17 y-1, no matter they were from single sources (14:0 presumably from marine OM and ai-15:0, i-15:0, 15:0 from bacterial OM) or mixed sources (16:0). Meanwhile fatty acids with more carbon numbers, either 18:0 and 24:0 from mixed sources, or 26:0 and 28:0 presumably from terrestrial input, were less varied in concentrations with depth. This demonstrates a preferential decomposition of labile fatty acids during the early diagenesis of coastal sediment organic matter. A decrease of labile fatty acids δ13C values was observed with the decomposition, from which kinetic isotope fractionations were predicted ranging from 0.7 to 1.5‰. This provides an isotopic constraint of the mixing model to quantify labile organic matter from terrestrial input and local phytoplankton production, from which declined contribution of local phytoplankton production to labile fatty acids was identified in more recent sediment. This finding together with the low organic carbon content and rapid removal of fatty acids in the top sediment, demonstrates the poor preservation of labile organic matter on the shelf of NSCS, implying that the increasing primary production has not enhanced the coastal carbon sequestration yet, but rather leads to more intensified respiration with a potential risk to increase the CO2 outgassing from the coastal oceans.